Media literacy and young people’s integrity in political participation: a structural equation modelling approach - Maizatul Haizan Mahbob; Mohd Sufiean Hassan; Siti Nurshahidah Sah Allam; Fazurah Mustaffa; Noor Afzaliza Nazira Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
The unethical activities related to weak political participation integrity on social media have influenced negative behaviours among supporters, particularly the young people. Social media transmits information on demonstration activities by enabling the creation, collection, and dissemination of false information or seditious libel, which exposes the country to external attacks and threats. Furthermore, young people’s negative political participation activities on social media, such as creating and disseminating false information, making harsh remarks, generating turmoil to acquire popularity or go viral, can potentially lead to cybercrimes. This research identified the impacts of media literacy competencies, namely access, analysis and evaluation, creation, reflection, and action, on political participation integrity among young people. This study distributed a survey to targeted university students in Melaka, Malaysia using the simple random sampling method. The students’ participation was purely voluntary. A total of 388 responses were successfully collected. The structural equation authenticated that four competencies significantly influenced the participants’ political participation integrity: access, analysis and evaluation, reflection, and action. In addition, young people who have media literacy skills showed a stronger preference to engage in political activities with higher moral conduct. The findings provided valuable insights about young people's political participation integrity on social media in Malaysia.